2020
DOI: 10.14494/jnrs.20.1
|View full text |Cite
|
Sign up to set email alerts
|

Plutonium Isotopes Research in the Marine Environment: A synthesis

Abstract: Plutonium (Pu) isotopes are one of most important artificial radionuclides. Recent advances in analytical methodology of Pu have enabled Pu to play a vital role in tracing biogenic elements and pollutants transport, sediment deposition/resuspension and other marine process. The various ratios of Pu isotopes ( 238 Pu, 239 Pu, 240 Pu and 241 Pu), which are depende nt on the Pu sources, are useful for identifying the contributions from different sources, and these ratios can be utilized to indicate the marine pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 150 publications
0
2
0
Order By: Relevance
“…Globally speaking, since most nuclear factories and test sites are located in the northern hemisphere, the radioactivity level in the ocean of the northern hemisphere is higher than that of the southern hemisphere, while the radionuclide content decreases gradually with the increase of water depth in the vertical distribution; In 2000, the activities of 137Cs and 90Sr in ocean surface water were 2Bq / L. [2] However, due to the impact of nuclear facility discharge and nuclear accident, the nuclear pollution in some sea areas was significant, resulting in the activities of 137Cs and 90Sr in some marginal sea water bodies reaching tens of Baker per liter. By measuring the content of 137Cs in seawater, some foreign experts found that, under the influence of BNFL nuclear fuel company in the northeast of the Irish sea, the content closest to the sewage outlet was hundreds of times higher than that at the sea inlet.…”
Section: The Status Quo Of Marine Nuclear Pollutionmentioning
confidence: 99%
“…Globally speaking, since most nuclear factories and test sites are located in the northern hemisphere, the radioactivity level in the ocean of the northern hemisphere is higher than that of the southern hemisphere, while the radionuclide content decreases gradually with the increase of water depth in the vertical distribution; In 2000, the activities of 137Cs and 90Sr in ocean surface water were 2Bq / L. [2] However, due to the impact of nuclear facility discharge and nuclear accident, the nuclear pollution in some sea areas was significant, resulting in the activities of 137Cs and 90Sr in some marginal sea water bodies reaching tens of Baker per liter. By measuring the content of 137Cs in seawater, some foreign experts found that, under the influence of BNFL nuclear fuel company in the northeast of the Irish sea, the content closest to the sewage outlet was hundreds of times higher than that at the sea inlet.…”
Section: The Status Quo Of Marine Nuclear Pollutionmentioning
confidence: 99%
“…Leaching by rainfall flows and erosion processes initiate the transfer of 239,240 Pu with river waters from the entire catchment to the river mouth. The migration of soil particles ensures the transport of plutonium from watersheds to bottom sediments in coastal regions and estuaries [5]. For example, the contribution of plutonium from the global fallout to the Yellow River has been estimated to be 21±7×10 9 Bq/yr, with an average plutonium inventory in soil of 57±25 Bq/m 2 [6].…”
Section: Introductionmentioning
confidence: 99%